The impacts of destination personality and electronic word-of-mouth on tourists destination choice - Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim; Abdul Aziz, Yuhanis (Universiti Putra Malaysia, 2023)
The main aim of this research is to examine the influences of destination personality and electronic word-of-mouth in the context of destination selection decision-making. It also examines the influence of environmental sustainability on individuals’ sense of satisfaction and the mediating role of satisfaction in the context of destination choice and its subsequent effect on revisit intention. Langkawi’s designation as a UNESCO Geopark underscores its significance in terms of environmental sustainability, which is a primary focus of this study. The findings indicate a significant roles of personality traits of a destination and the electronic word-of-mouth communicated by individuals in decision-making process for selecting a destination. Additionally, the findings reveal that satisfaction plays a mediating role in the relationship between destination selection and the desire to engage in future visits.